Oxygen-Containing Nanoclusters on the Surface of Pt-Electrodes and Oxygen Reduction Reaction in Alkaline Medium - Aleksey M. Trunov (International Journal of Electrochemistry)
Analysis of the role of oxygen-containing nanoclusters in oxygen reduction reaction (ORR) on Pt-electrodes in alkaline media is provided on the basis of the concept of electrochemical processes with slowed stage of consecutive heterogeneous chemical reaction (ConHCR). Under the ConHCR concept, the main factor determining the ORR characteristics is energetic inhomogeneity of electrode surface (EIES) according to Temkin. A new concept, according to which EIES is determined by the Gibbs energy of formation of oxygen-containing surface structures with inclusions of surface defects of the platinum crystal structure, Pts,d, is formulated. A correlation between the level of EIES of Pt-electrodes and packing density of Pts,d atoms on the surface of Pt(hkl) monocrystals is determined. The concept, according to which the stationary potential of ORR process is considered as a “mixed potential” of two reactions (electrochemical reduction of surface atom PtIIs,d and consecutive oxidation of PtIs,d by molecular oxygen), is substantiated. It is proposed that the formation of surface nanocluster transition state [⁎(OO)PtIIs,d(OH)] defines the rate of the entire ORR process on Pt-electrodes in alkaline media.